2022
DOI: 10.7759/cureus.28643
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Rapidly Progressive Coccidioidal Meningitis in an Immunocompetent Patient

Abstract: A 50-year-old male with a history of a dull headache and neck pain for a few weeks presented to the ER with complaints of progressive weakness and difficulty walking. Physical examination revealed a lethargic, confused patient with abnormal tremors at rest. Initial lab work was significant for elevated hemoglobin, hematocrit, and hyponatremia. Additionally, CT imaging was significant for prominent ventricles. Several serologies and polymerase chain reaction (PCR) tests were ordered to determine the etiology of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…1 The majority were previously healthy, with no known immune deficiencies, consistent with other case series. 6,8,10,11 Recent reports have documented specific gene mutations which alter interleukin 12, interferon-gamma, and other cellular immune responses, and are associated with an increased risk of disseminated coccidioidomycosis, but these were not tested for in our patients. [12][13][14] Altered balance between type 2 immune response and interferon gammamediated type 1 immune response has been shown to increase susceptibility to disseminated coccidioidomycosis.…”
Section: Discussionmentioning
confidence: 97%
“…1 The majority were previously healthy, with no known immune deficiencies, consistent with other case series. 6,8,10,11 Recent reports have documented specific gene mutations which alter interleukin 12, interferon-gamma, and other cellular immune responses, and are associated with an increased risk of disseminated coccidioidomycosis, but these were not tested for in our patients. [12][13][14] Altered balance between type 2 immune response and interferon gammamediated type 1 immune response has been shown to increase susceptibility to disseminated coccidioidomycosis.…”
Section: Discussionmentioning
confidence: 97%
“…Few reports demonstrate rapidly disseminated infections in immunocompetent patients. Fatima et al reported an immunocompetent individual with early manifestations of CM who received early treatment that prevented neurological sequelae [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of the population with these conditions is increasing, which means the number of persons at risk for severe coccidioidomycosis is also on the rise [ 28 ]. Apart from host status, severe disease does occur in people with no recognized immunocompromising disorder, too [ 29 ]. The potential for severe outcomes, especially among the increasing numbers of vulnerable and immunocompromised populations, is amplified when the diagnosis is delayed.…”
Section: Clinical Benefits Of Coccidioidomycosis As a Reportable Diseasementioning
confidence: 99%